2013
DOI: 10.1016/j.atmosenv.2013.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation of 4-phenoxyphenol sensitised by 4-carboxybenzophenone: Evidence of new photochemical pathways in the bulk aqueous phase and on the surface of aerosol deliquescent particles

Abstract: Phototransformation of 4-phenoxyphenol sensitised by 4-carboxybenzophenone in aqueous solution and at the aerosol interface: Evidence of new photochemical pathways in the bulk aqueous phase and on the surface of aerosol deliquescent particles. Atmos. Environ. 2013, 81, 569-578. DOI: 10.1016/j.atmosenv.2013 You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions:(1) You may use this AAM for non-commercial purposes only un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Heterogeneous reactivity of 4-phenoxyphenol towards ozone was significantly enhanced in the presence of aromatic ketones (4-carboxybenzophenone) under light irradiation compared to the dark ozone reaction (Net et al, 2010d). This photosensitized reaction proceeds through the electron transfer reaction to ozone with formation of an ozonide anion (O − 3 ) which can further react to produce OH radicals (De Laurentiis et al, 2013), and the formation of OH radicals was confirmed during such photochemical processing on the silica particles. The same group (Net et al, 2009) proposed a comprehensive reaction mechanism based on identified products arising from the OH-addition to 4-phenoxyphenol.…”
Section: Kc-msmentioning
confidence: 90%
“…Heterogeneous reactivity of 4-phenoxyphenol towards ozone was significantly enhanced in the presence of aromatic ketones (4-carboxybenzophenone) under light irradiation compared to the dark ozone reaction (Net et al, 2010d). This photosensitized reaction proceeds through the electron transfer reaction to ozone with formation of an ozonide anion (O − 3 ) which can further react to produce OH radicals (De Laurentiis et al, 2013), and the formation of OH radicals was confirmed during such photochemical processing on the silica particles. The same group (Net et al, 2009) proposed a comprehensive reaction mechanism based on identified products arising from the OH-addition to 4-phenoxyphenol.…”
Section: Kc-msmentioning
confidence: 90%
“…The adsorption of the pesticide can influence K ðO3Þ and the nature of the adsorption sites. In addition, the relative humidity is an important parameter that has not been much studied (De Laurentiis et al, 2013) but that may influence the partitioning of ozone between the gas phase and the particle surface.…”
Section: Pesticidesmentioning
confidence: 99%
“…The triplet states of benzophenones often behave as effective photosensitisers for the transformation of phenolic compounds. 46,47 The reactivity between 3 4BPOH* and phenol was assessed by studying the effect of phenol concentration on the value of k 520 nm in acetonitrile. The value of k 520 nm increases linearly with increasing phenol (see Fig.…”
Section: Resultsmentioning
confidence: 99%